Al2O3 / MXene composite ceramic layer and preparation method and application thereof
By preparing the Al2O3/MXene composite ceramic layer by microarc oxidation method on the surface of the aluminum alloy, the corrosion and wear problems of aluminum alloy in harsh environments are solved, and significantly improved corrosion resistance and wear resistance are achieved, providing high-efficiency aluminum Alloy surface protection scheme.
Patent Information
- Application Number
- CN202411261164.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-27
AI Technical Summary
Aluminum alloys are prone to damage to the surface passivation film in harsh environments, resulting in corrosion and wear problems. The existing technology methods are costly or affect the performance of the substrate, and the corrosion and wear resistance are insufficient.
The Al2O3/MXene composite ceramic layer was prepared by microarc oxidation method. By doping MXene nanoparticles into the coating, the corrosion resistance of the ceramic layer was improved by using its excellent barrier properties and reducing the influence of discharge channels and microcracks.
The corrosion resistance of aluminum alloy is significantly improved, the self-corrosion current is reduced by nearly three orders of magnitude, the corrosion resistance is increased by nearly 1,000 times, and the process is simple and the performance is repeatable.
Smart Images

Figure HDA0005035697690000011 
Figure HDA0005035697690000012 
Figure HDA0005035697690000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials, in particular to Al 2 O 3 / MXene composite ceramic layer and its preparation method and application. Background Art
[0002] Aluminum alloys are widely used in aerospace, ships, armored equipment, electronic equipment and other fields because of their low density, high specific strength, and good electrical and thermal conductivity. Under natural conditions, a dense passivation film can be formed on the surface of aluminum alloys, which plays a certain protective role, but the thickness of this passivation layer is not large and the wear resistance is not high. In harsh environments such as the ocean, the salt content is high, the seawater and sea breeze erode violently, and the temperature, pressure and other environmental factors are harsh. The passivation film on the surface of aluminum alloys is easily damaged. Therefore, during its service, parts corrosion and wear problems often occur, which seriously affect the life of aluminum alloy equipment. Although researchers have tried many methods to improve its corrosion resistance and friction resistance, including using different alloying elements, using anti-corrosion coatings, or improving its performance through heat treatment and other surface treatment technologies. However, these methods all have some shortcomings. For example, anti-corrosion paint coatings are easily damaged by external wear, which leads to decreased corrosion resistance and coating failure. Coatings prepared by PVD technology have good wear and corrosion resistance, but the technical cost is high and it is not convenient to handle complex workpieces. Ion penetration and heat treatment rely on high temperature conditions, which can easily affect the overall performance of the substrate, etc. Summary of the invention
[0003] In view of the above problems, the present invention provides an Al 2 O 3 / MXene composite ceramic layer, the Al 2 O 3 The / MXene composite ceramic layer reduces the impact of discharge channels (holes) and microcracks formed on the surface of the aluminum alloy due to micro-arc oxidation, and improves the corrosion resistance of the aluminum alloy.
[0004] In order to achieve the above object, the present invention provides an Al 2 O 3 / MXene composite ceramic layer is mainly prepared by aluminum alloy and MXene nanoparticles through micro-arc oxidation method.
[0005] Micro-arc oxidation technology (MAO) is also called plasma electrolytic oxidation (PEO). This technology has the advantages of low pretreatment requirements, simple process, and low environmental pollution. The coating made by micro-arc oxidation technology has good bonding strength between the film layer and the substrate, high toughness, excellent wear resistance, corrosion resistance, biocompatibility and other characteristics, and meets the needs of green development. However, previous studies have found that due to the existence of violent plasma discharge and gas precipitation in the micro-arc oxidation process, the surface of the ceramic layer inevitably has defects such as micropores and cracks. Therefore, on the basis of the micro-arc oxidation method, a technical problem of how to improve the corrosion resistance and wear resistance of the coating is further proposed. In response to this technical problem, the inventors proposed to improve the coating performance by doping micro-nano particle materials in the coating structure, introducing two-dimensional nanomaterials MXene, and using the excellent barrier properties of MXene to improve the impermeability of the micro-arc oxidation coating in seawater, thereby improving the corrosion resistance of the micro-arc oxidation coating, and the prepared Al 2 O 3 / MXene composite ceramic layer Figure 1 shown.
[0006] The present invention also provides a method having Al 2 O 3 The method for preparing an aluminum alloy with a / MXene composite ceramic layer comprises the following steps: placing the aluminum alloy in an electrolyte for micro-arc oxidation to obtain the aluminum alloy having the Al 2 O 3 Aluminum alloy / MXene composite ceramic layer.
[0007] The above-mentioned micro-arc oxidation is carried out on a customized micro-arc oxidation power supply system, in which the aluminum alloy is used as the anode, the stainless steel container is used as the cathode, and the cooling system and the mechanical stirrer keep the electrolyte temperature below 50° C. It can be understood that the amount of the aluminum alloy and the electrolyte is selected by those skilled in the art according to the conventional technical knowledge in the art.
[0008] In one embodiment, the electrolyte includes MXene nanoparticles, silicate, phosphate and alkali.
[0009] In one of the embodiments, in the electrolyte, the concentration of the MXene nanoparticles is 0.05 g / L to 0.25 g / L, the concentration of the silicate is 5 g / L to 10 g / L, the concentration of the phosphate is 10 g / L to 15 g / L, and the concentration of the alkali is 1 g / L to 2 g / L.
[0010] It is understandable that those skilled in the art can prepare a mother solution or a reserve solution with a higher concentration when preparing the above-mentioned electrolyte, and then dilute it when it is used. The mother solution or the reserve solution and its concentration are all within the protection scope of the present invention.
[0011] In one embodiment, the silicate comprises sodium silicate, the phosphate comprises sodium hexametaphosphate, and the alkali comprises sodium hydroxide.
[0012] In one embodiment, the reaction conditions of the micro-arc oxidation include: stirring the electrolyte, using a constant current mode, and a forward output current density of 4A / dm 2 ~10A / dm 2 The oxidation time is 10min to 20min, the frequency is 200Hz to 1000Hz, and the forward duty cycle is 10% to 50%.
[0013] In one embodiment, the stirring speed is 150 rad / min to 250 rad / min, and the temperature of the electrolyte is 10 to 50°C.
[0014] In one embodiment, the preparation method further includes aluminum alloy pretreatment and electrolyte preparation before micro-arc oxidation.
[0015] In one embodiment, the aluminum alloy pretreatment includes: grinding, cleaning, and drying the aluminum alloy surface.
[0016] In one of the embodiments, the polishing includes step-by-step polishing using 400# to 2000# SiC sandpaper; the cleaning includes cleaning using deionized water and anhydrous ethanol; and the drying includes drying with warm air.
[0017] In one embodiment, the preparation of the electrolyte includes: ultrasonically treating the electrolyte and mechanically stirring the electrolyte to achieve full dissolution of the electrolyte.
[0018] The invention also provides the aluminum alloy obtained by the preparation method.
[0019] In one embodiment, the Al 2 O 3 / MXene composite ceramic layer or the Al alloy 2 O 3 The thickness of the / MXene composite ceramic layer is 6μm to 10μm.
[0020] The present invention also provides the Al 2 O 3 Application of / MXene composite ceramic layer or the aluminum alloy in aerospace equipment and navigation equipment.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The Al of the present invention 2 O 3 / MXene composite ceramic layer and preparation method and application thereof, the Al 2 O 3 The / MXene composite ceramic layer reduces the impact of discharge channels (holes) and microcracks formed on the surface of aluminum alloys due to micro-arc oxidation, and improves the corrosion resistance of aluminum alloys. The best performance aluminum alloy sample obtained by the preparation method of this case has a self-corrosion current reduced by nearly three orders of magnitude in electrochemical testing, and the corrosion resistance is improved by nearly 1000 times, which has strong corrosion resistance. In addition, the preparation method of the present invention is simple and has strong performance repeatability, which provides reference and reference value for enhancing the durability of aluminum alloys in complex environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The Al 2 O 3 Schematic diagram of the structure of / MXene composite ceramic layer;
[0024] Figure 2 Example 1: Preparation of Al by micro-arc oxidation on the surface of aluminum alloy 2 O 3 X-ray diffraction pattern comparison diagram (XRD diagram) of the / MXene composite ceramic layer, the micro-arc oxidation ceramic layer of comparative example 1, and the aluminum alloy substrate, wherein the Al doped with Example 1 2 O 3 / MXene composite ceramic layer, the undoped ceramic layer is the ceramic layer of Comparative Example 1, and the substrate is an aluminum alloy substrate;
[0025] Figure 3 Example 1: Preparation of Al by micro-arc oxidation on the surface of aluminum alloy 2 O 3 The morphology comparison diagram (SEM morphology diagram) of the / MXene composite ceramic layer, the micro-arc oxidation ceramic layer of comparative example 1, and the aluminum alloy substrate is shown in FIG. 2 O 3 / MXene composite ceramic layer, the undoped ceramic layer is the ceramic layer of Comparative Example 1, and the substrate is an aluminum alloy substrate;
[0026] Figure 4 Example 1: Preparation of Al by micro-arc oxidation on the surface of aluminum alloy 2 O 3 Energy dispersion spectrum (EDS spectrum) of / MXene composite ceramic layer;
[0027] Figure 5The energy dispersion spectrum (EDS spectrum) of the micro-arc oxidation ceramic layer of Comparative Example 1;
[0028] Figure 6 Example 1: Preparation of Al by micro-arc oxidation on the surface of aluminum alloy 2 O 3 Polarization curve comparison of the micro-arc oxidation ceramic layer and the aluminum alloy substrate of Example 1, wherein the Al doped with Example 1 2 O 3 / MXene composite ceramic layer, the undoped ceramic layer is the ceramic layer of Comparative Example 1, and the substrate is an aluminum alloy substrate;
[0029] Figure 7 For Comparative Example 2, Al was prepared by micro-arc oxidation on the surface of aluminum alloy. 2 O 3 / SiO 2 Polarization curves of the composite ceramic layer. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0032] source:
[0033] Unless otherwise specified, the reagents, materials, and equipment used in this example are all commercially available; the experimental methods are all conventional experimental methods in the art unless otherwise specified.
[0034] Example 1
[0035] Al 2 O 3 / MXene composite ceramic layer and preparation method thereof.
[0036] A method for preparing Al on the surface of aluminum alloy by micro-arc oxidation 2 O 3 The method for forming a composite ceramic layer of MXene comprises the following steps:
[0037] S1. The surface of 6061 series aluminum alloy is polished step by step with 400#, 800#, 1200#, and 2000# SiC sandpaper, then cleaned and dried with deionized water and anhydrous ethanol, and sealed and stored in a sample bag after drying;
[0038] S2. Prepare electrolyte with deionized water. The electrolyte components include 10 g / L sodium silicate, 15 g / L sodium hexametaphosphate, 2 g / L sodium hydroxide and 0.1 g / L MXene nanoparticles. Before the micro-arc oxidation experiment, the electrolyte in the 304 stainless steel container as the cathode was mechanically stirred at 800 rad / min for 30 min.
[0039] S3. The aluminum alloy substrate treated in S1 is subjected to micro-arc oxidation treatment in the electrolyte treated in S2 to obtain a composite ceramic layer doped with MXene.
[0040] The micro-arc oxidation power supply adopts constant current mode, and the forward output current density is 7A / dm 2 , oxidation time 15min, frequency 400Hz, forward duty cycle 40%, rotor speed in electrolyte 200rad / min, electrolyte temperature maintained at 10℃~50℃; after sample preparation, take out the sample, wash with deionized water and ethanol and dry, and seal and store in a sample bag after drying;
[0041] The relevant performance data of this embodiment are as follows: The self-corrosion current density of the micro-arc oxidation composite ceramic layer doped with MXene after being immersed in a 3.5wt% sodium chloride solution for 120min is 10 -10 A / cm 2 , which is 3 orders of magnitude lower than that of the base aluminum alloy.
[0042] Example 2
[0043] Al 2 O 3 / MXene composite ceramic layer and preparation method thereof.
[0044] A method for preparing Al on the surface of aluminum alloy by micro-arc oxidation 2 O 3 The method for forming a composite ceramic layer of MXene comprises the following steps:
[0045] S1. The surface of 6061 series aluminum alloy is polished step by step with 400#, 800#, 1200#, and 2000# SiC sandpaper, then cleaned and dried with deionized water and anhydrous ethanol, and sealed and stored in a sample bag after drying;
[0046] S2. Prepare electrolyte with deionized water. The electrolyte components include 10 g / L sodium silicate, 15 g / L sodium hexametaphosphate, 2 g / L sodium hydroxide and 0.2 g / L MXene nanoparticles. Before the micro-arc oxidation experiment, the electrolyte in the 304 stainless steel container as the cathode was mechanically stirred at 800 rad / min for 30 minutes.
[0047] S3. The aluminum alloy substrate treated in S1 is subjected to micro-arc oxidation treatment in the electrolyte treated in S2 to obtain a composite ceramic layer doped with MXene.
[0048] The micro-arc oxidation power supply adopts constant current mode, and the forward output current density is 7A / dm 2 , oxidation time 15min, frequency 400Hz, forward duty cycle 40%, rotor speed in electrolyte 200rad / min, electrolyte temperature maintained at 10℃~50℃; after sample preparation, take out the sample, wash with deionized water and ethanol and dry, and seal and store in a sample bag after drying;
[0049] The relevant performance data of this embodiment are as follows: The self-corrosion current density of the micro-arc oxidation composite ceramic layer doped with MXene after being immersed in a 3.5wt% sodium chloride solution for 120min is 10 -10 A / cm 2 , which is 3 orders of magnitude lower than that of the base aluminum alloy.
[0050] Example 3
[0051] Al 2 O 3 / MXene composite ceramic layer and preparation method thereof.
[0052] A method for preparing Al on the surface of aluminum alloy by micro-arc oxidation 2 O 3 The method for forming a composite ceramic layer of MXene comprises the following steps:
[0053] S1. The surface of 7075 series aluminum alloy is polished step by step with 400#, 800#, 1200#, and 2000# SiC sandpaper, then cleaned and dried with deionized water and anhydrous ethanol, and sealed and stored in a sample bag after drying;
[0054] S2. Prepare electrolyte with deionized water. The electrolyte components include 10 g / L sodium silicate, 15 g / L sodium hexametaphosphate, 2 g / L sodium hydroxide and 0.1 g / L MXene nanoparticles. Before the micro-arc oxidation experiment, the electrolyte in the 304 stainless steel container as the cathode was mechanically stirred at 800 rad / min for 30 min.
[0055] S3. The aluminum alloy substrate treated in S1 is subjected to micro-arc oxidation treatment in the electrolyte treated in S2 to obtain a composite ceramic layer doped with MXene.
[0056] The micro-arc oxidation power supply adopts constant current mode, and the forward output current density is 7A / dm 2 , oxidation time 15min, frequency 400Hz, forward duty cycle 40%, rotor speed in electrolyte 200rad / min, electrolyte temperature maintained at 10℃~50℃; after sample preparation, take out the sample, wash with deionized water and ethanol and dry, and seal and store in a sample bag after drying;
[0057] The relevant performance data of this embodiment are as follows: The self-corrosion current density of the micro-arc oxidation composite ceramic layer doped with MXene after being immersed in a 3.5wt% sodium chloride solution for 120min is 10 -10 A / cm 2 , which is 3 orders of magnitude lower than that of the base aluminum alloy.
[0058] Comparative Example 1
[0059] A method for preparing Al on the surface of aluminum alloy by micro-arc oxidation 2 O 3 A method for producing a ceramic layer, comprising the steps of:
[0060] S1. The surface of 6061 series aluminum alloy is polished step by step with 400#, 800#, 1200#, and 2000# SiC sandpaper, then cleaned and dried with deionized water and anhydrous ethanol, and sealed and stored in a sample bag after drying;
[0061] S2. Prepare electrolyte with deionized water. The electrolyte components include 10 g / L sodium silicate, 15 g / L sodium hexametaphosphate and 2 g / L sodium hydroxide. No MXene nanoparticles are added. Before the micro-arc oxidation experiment, the electrolyte in the 304 stainless steel container as the cathode is mechanically stirred at a speed of 800 rad / min for 30 minutes.
[0062] S3. The aluminum alloy substrate treated in S1 is subjected to micro-arc oxidation treatment in the electrolyte treated in S2 to obtain a ceramic layer.
[0063] The micro-arc oxidation power supply adopts constant current mode, and the forward output current density is 7A / dm 2 , oxidation time 15min, frequency 400Hz, forward duty cycle 40%, rotor speed in electrolyte 200rad / min, electrolyte temperature maintained at 10℃~50℃; after sample preparation, take out the sample, wash with deionized water and ethanol and dry, and seal and store in a sample bag after drying;
[0064] The relevant performance data of this comparative example are as follows: The self-corrosion current density of the micro-arc oxidation ceramic layer after being immersed in a 3.5wt% sodium chloride solution for 120min is 10 -8 A / cm 2 , which is one order of magnitude lower than that of the base aluminum alloy.
[0065] The properties of the ceramic layer prepared in Example 1 and Comparative Example 1 are as follows: Figure 2-6 shown.
[0066] Comparative Example 2
[0067] A method for preparing Al on the surface of aluminum alloy by micro-arc oxidation 2 O 3 / SiO 2 The method for composite ceramic layer comprises the following steps:
[0068] S1. The surface of 7075 series aluminum alloy is polished step by step with 400#, 800#, 1200#, and 2000# SiC sandpaper, then cleaned and dried with deionized water and anhydrous ethanol, and sealed and stored in a sample bag after drying;
[0069] S2, prepare electrolyte with deionized water, the electrolyte components include 10g / L sodium silicate, 15g / L sodium hexametaphosphate, 2g / L sodium hydroxide and 0.1g / L SiO 2 Nanoparticles. Before the micro-arc oxidation experiment, the electrolyte in the 304 stainless steel container as the cathode was mechanically stirred at a speed of 800 rad / min for 30 minutes;
[0070] S3, the aluminum alloy substrate treated in S1 is subjected to micro-arc oxidation in the electrolyte treated in S2 to obtain doped SiO 2 Composite ceramic layer of nanoparticles.
[0071] The micro-arc oxidation power supply adopts constant current mode, and the forward output current density is 7A / dm 2 , oxidation time 15min, frequency 400Hz, forward duty cycle 40%, rotor speed in electrolyte 200rad / min, electrolyte temperature maintained at 10℃~50℃; after sample preparation, take out the sample, wash with deionized water and ethanol and dry, and seal and store in a sample bag after drying;
[0072] The relevant performance data of this comparative example are as follows: doped SiO 2 The self-corrosion current density of the nanoparticle micro-arc oxidation composite ceramic layer was 10 -10 A / cm 2 , which is 2 orders of magnitude lower than that of the base aluminum alloy.
[0073] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0074] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An Al2O3 / MXene composite ceramic layer, characterized in that: It is mainly prepared from aluminum alloy and MXene nanoparticles by micro-arc oxidation.
2. A method for preparing an aluminum alloy having an Al2O3 / MXene composite ceramic layer, characterized in that: The following steps are involved: The aluminum alloy is placed in an electrolyte for micro-arc oxidation to obtain an aluminum alloy having the Al2O3 / MXene composite ceramic layer as claimed in claim 1.
3. The preparation method according to claim 2, characterized in that: The electrolyte includes MXene nanoparticles, silicate, phosphate and alkali.
4. The preparation method according to claim 3, characterized in that: In the electrolyte, the concentration of the MXene nanoparticles is 0.05 g / L to 0.25 g / L, the concentration of the silicate is 5 g / L to 10 g / L, the concentration of the phosphate is 10 g / L to 15 g / L, and the concentration of the alkali is 1 g / L to 2 g / L.
5. The preparation method according to claim 3, characterized in that: The silicate includes sodium silicate, the phosphate includes sodium hexametaphosphate, and the alkali includes sodium hydroxide.
6. The preparation method according to claim 2, characterized in that: The reaction conditions of the micro-arc oxidation include: stirring the electrolyte, using a constant current mode, and a forward output current density of 4A / dm 2 ~10A / dm 2 The oxidation time is 10min to 20min, the frequency is 200Hz to 1000Hz, and the forward duty cycle is 10% to 50%.
7. The preparation method according to claim 6, characterized in that: The stirring speed is 150 rad / min to 250 rad / min, and the temperature of the electrolyte is 10 to 50°C.
8. The preparation method according to any one of claims 2 to 7, characterized in that: The preparation method also includes aluminum alloy pretreatment and electrolyte preparation before micro-arc oxidation.
9. The aluminum alloy obtained by the preparation method according to any one of claims 2 to 8.
10. Application of the Al2O3 / MXene composite ceramic layer according to claim 1 or the aluminum alloy according to claim 9 in aerospace equipment and marine equipment.
Citation Information
Cited By
Composite film layer of titanium alloy as well as preparation method and application of composite film layer
CN120231110A
